Exploring the essential factors of performance improvement in sludge membrane bioreactor technology coupled with symbiotic algae. (15th August 2020) - Sun, Li; Ma, Jinxing; Li, Lipin; Tian, Yu; Zhang, Zhong; Liao, Huaiyu; Li, Jibin; Tang, Wangwang; He, Di
Abstract: In this study, a coupled system of algal-sludge and membrane bioreactor (AS-MBR) was established for fouling control, and meanwhile the performance of wastewater treatment was enhanced. Results indicated that the AS-MBR increased the COD, NH4 + -N, TN and PO4 3- -P removal efficiencies from 91.7% to 95.9%, 90.8%–96.9%, 22.0% to 34.3% and 18.4%–32.6%, respectively. Further analysis suggested that in the AS-MBR, the total specific oxygen utilization rate (SOUR), the SOUR of ammonia oxidizing bacteria and the SOUR of nitrite oxidizing bacteria were 26.6%, 58.5% and 52.4% higher than the control, respectively, indicating the improvement of microbial activities in AS-MBR. Additionally, the membrane fouling rates in the AS-MBR were 52.6% and 32.2% lower than the control in the slow and rapid fouling processes, respectively. A further mechanism investigation demonstrated that the concentrations of extracellular polymeric substance (EPS) were decreased by 19.8% and 22.1% in the mixed liquid and the fouling layer, respectively, after the inoculation of algae, which was expected to have a positive effect on the higher permeability and longer operation cycle of the membrane in the AS-MBR. More regular floc morphology was observed for the fouling layer on the membrane of AS-MBR, with the polysaccharides and proteins forming large clusters and channels in the fouling layer that likely decreased the filtration resistance. Consequently, high-throughput sequencing analysis revealed that the microbial community in the AS-MBR had higher abundances of bacteria and algae related to nutrients and organic matters degradation, which was beneficial for the improvement of wastewater treatment and alleviation of membrane fouling. Graphical abstract: Image 1 Highlights: The AS-MBR was favorable to removal nutrients and membrane fouling mitigation. . The dramatic decrease of EPS was achieved both in liquid and fouling layer of AS-MBR. . The morphology and topography of fouling layer were improved after algal inoculation. . The functional bacteria were enriched and the bioactivity was enhanced in the AS-MBR. .